Tax Avoidance Analysis: The Role of Biological Asset Intensity, Leverage, and Profitability in Agricultural Companies - Puji Rahayu (JURNAL ECONOMINA, 2026)
Global economic pressures and the complexity of tax regulations are driving agricultural companies to manage their tax obligations more efficiently, including through tax avoidance practices. This study aims to analyze the influence of biological asset intensity, leverage, and profitability on tax avoidance in agricultural companies. The study used a quantitative approach with panel data regression analysis using the E-Views 12 application. The results show that biological asset intensity and leverage have no significant effect on tax avoidance, while profitability has a negative effect on tax avoidance. Simultaneously, all three independent variables influence tax avoidance. These findings can provide input for companies and tax authorities in improving tax compliance in the agricultural sector